Towards an incentive‐compatible, reputation‐based framework for stimulating cooperation in opportunistic networks: a survey. Issue 6 (1st November 2017) - Mantas, Nikolaos; Louta, Malamati; Karapistoli, Eirini; Karetsos, George T.; Kraounakis, Stylianos; Obaidat, Mohammad S.
Abstract : In opportunistic networks (OppNets), routing and data forwarding among mobile devices are facilitated by relays or next‐hop forwarders. To guarantee end‐to‐end data delivery it is important to provide participation. However, in sparsely connected OppNets, it is extremely challenging to monitor the behaviour of the relays and identify selfish/malicious relays cooperating with each other in order to forge routing information or drop useful data. Cooperation enforcement schemes are seen as a lightweight alternative to conventional secure forwarding techniques that involve cryptographically signed certificate exchanges, providing a 'softer' security layer to protect basic networking operations. In general, cooperation enforcement schemes fall into two broad categories: trust establishment via a reputation system and pricing or credit‐based schemes. This study offers a comprehensive survey of representative cooperation enforcement schemes that exploit a reputation system. The authors analyse their distinct features, identify and discuss critical challenges that should be efficiently addressed when designing such mechanisms, indicating at the same time potential solutions and provide an informative table to display the authors' findings. From this analysis, they examine issues and concerns surrounding the field of cooperation enforcement in OppNets, and provide guidelines and directions for future researchers.